Handbook of temporal reasoning in artificial intelligence - Fisher, Michael, 1962-; Gabbay, Dov M., 1945-; Vila, L. (Lluis) (Foundations of artificial intelligence (Elsevier), 2005)
This collection represents the primary reference work for researchers and students in the area of Temporal Reasoning in Artificial Intelligence. Temporal reasoning has a vital role to play in many areas, particularly Artificial Intelligence. Yet, until now, there has been no single volume collecting together the breadth of work in this area. This collection brings together the leading researchers in a range of relevant areas and provides an coherent description of the breadth of activity concerning temporal reasoning in the filed of Artificial Intelligence. Key Features: - Broad range: foundations; techniques and applications - Leading researchers around the world have written the chapters - Covers many vital applications - Source book for Artificial Intelligence, temporal reasoning - Approaches provide foundation for many future software systems Broad range: foundations; techniques and applications Leading researchers around the world have written the chapters Covers many vital applications Source book for Artificial Intelligence, temporal reasoning Approaches provide foundation for many future software systems.